How apparatus difficulty scores affect all around results in mens artistic gymnastics - Cuk, I.; Forbes, W. (Science of Gymnastics Journal, 2010)
On a sample of 49all-around male gymnasts at the 2009 European Championships the implications of the difficulty scores were tested in relation to the success in all-around competition. After the regression, cluster and ANOVA analysis, three groups of quality all-around gymnasts were determined, while only one group had a chance to win an all-around medal; difficulty scores between all six apparatus were not equal; the highest prediction of the all-around score was the parallel bars difficulty score.